Expanding fashion exhibition history and theory: Fashion at New Zealand's national museum since 1950. (1st April 2014) - Labrum, Bronwyn
New Zealand museums, as opposed to art galleries, have been slow to exhibit fashion. Instead, fashion and decorative arts were part of human history collections and displays, emphasizing the country's colonial heritage. Yet museums have increasingly focused on fashion as a distinctive mode of display. This article traces the story of fashion and its display at New Zealand's national museum since 1950. It extends the notion of 'fashion' to include 'the fashionable'. It combines social as well as cultural history, and the material as well as the visual, aiming for a more robust theorization and analysis of fashion exhibition history.This account involves a shift from settler histories, honorary female museum professionals working in the background, and 'decorative arts', to the development of dedicated fashion galleries. These recognized New Zealand as situated in the Pacific with its own distinctive history of fashion and sat alongside international blockbuster exhibitions. New Zealand museums followed international trends, at a great distance from the centres of fashion and the famous world museums. They also brought a local sensibility and history that contrasts with, and sheds light on, the wider story of museum fashion.